Nobody knows where the blues come from : lyrics and history - Springer, Robert, 1946- (American made music series., 2006)
Musicians and music scholars rightly focus on the sounds of the blues and the colorful life stories of blues performers. Equally important and, until now, inadequately studied are the lyrics. The international contributors to Nobody Knows Where the Blues Come From explore this aspect of the blues and establish the significance of African American popular song as a neglected form of oral history. "High Water Everywhere: Blues and Gospel Commentary on the 1927 Mississippi River Flood," by David Evans, is the definitive study of songs about one of the greatest natural disasters in the history of.